Firm Productivity Moderated Link Between Human Capital and Compensation: The Significance of Task‐Specific Human Capital. Issue 3 (22nd May 2013) - Schulz, Eric; Chowdhury, Sanjib; Van de Voort, David
Abstract The human capital of a firm as manifested by employee knowledge and experience represents a key resource of a firm's capabilities. Prior empirical studies have found that firms composed of high levels of human capital experience superior firm performance. Human capital theory proposes that an individual's general or firm‐specific human capital is positively related to compensation. However, empirical studies examining firm‐specific human capital's association with higher employee compensation have been inconclusive. The current study proposes that firm‐specific human capital be categorized as task‐specific and non‐task‐specific. Employees accumulate task‐specific human capital through duties conducted in their current position. Non‐task‐specific human capital represents experiences gained in prior positions to an employee's current job within the firm. Utilizing human capital data from 38, 390 employees representing 76 firms in the IT sector, this study examines the association between forms of human capital and employee compensation at different levels of firm productivity. Results show that task‐specific human capital is associated with higher employee compensation. In addition, firm productivity moderates this association.